Targeting Behavior among Indonesian Firms: Two-Step Partial Adjustment Model Analysis - Cahyaningdyah, Dwi (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2019)
In this research, we tested the heterogeneity of speed of adjustment toward target leverage among industries on the Indonesian stock exchange by using two-step partial adjustment model. The sample collected from 2007-2016 and consisted of firms in eight sectors, i.e. agriculture, mining, basic industries, miscellaneous, consumer goods, property and real estate, infrastructure, utilities and transportation as well as trade, services and investment sectors. Firms in the financial industry are excluded because the capital structure of firms in the financial industry reflects specific regulations and are not independent firms’ policies. The results showed that speed of adjustment ranged from 61% - 45% for book leverage and 67% - 43% for market leverage. This significant speed of adjustment is consistent with trade-off theory, which states that firms have target leverage and when firms are deviated from the target, firms will make financial decisions that will close the gap between previous year’s leverage and the target leverage of current period.